2016
DOI: 10.4184/asj.2016.10.4.734
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Magnetic Resonance Imaging Findings between Pathologically Proven Cases of Atypical Tubercular Spine and Tumour Metastasis: A Retrospective Study in 40 Patients

Abstract: Study DesignRetrospective study.PurposeTo note the magnetic resonance imaging (MRI) differences between pathologically proven cases of atypical spinal tuberculosis and spinal metastasis in 40 cases.Overview of LiteratureSpinal tuberculosis, or Pott's spine, constitutes less than 1% of all cases of tuberculosis and can be associated with a neurologic deficit. Breast, prostate and lung cancer are responsible for more than 80% of metastatic bone disease cases, and spine is the most common site of bone metastasis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 13 publications
(16 reference statements)
0
24
0
Order By: Relevance
“…There are numerous similarities in the imaging and clinical manifestations between noncontiguous vertebral TB, a neoplastic disease, lymphoma, and multiple myeloma; however, differentiation requires the presence of a combination of general symptoms, laboratory test results, appropriate radiological results, and the physician's experience. [ 17 , 22 , 23 ] The appearance of vertebral lymphoma at MRI can be nonspecific. However, lesions showing bone marrow replacement and a surrounding soft-tissue mass without large areas of cortical bone destruction suggest lymphoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are numerous similarities in the imaging and clinical manifestations between noncontiguous vertebral TB, a neoplastic disease, lymphoma, and multiple myeloma; however, differentiation requires the presence of a combination of general symptoms, laboratory test results, appropriate radiological results, and the physician's experience. [ 17 , 22 , 23 ] The appearance of vertebral lymphoma at MRI can be nonspecific. However, lesions showing bone marrow replacement and a surrounding soft-tissue mass without large areas of cortical bone destruction suggest lymphoma.…”
Section: Discussionmentioning
confidence: 99%
“…[ 21 ] In neoplastic involvement of the spine, the disc spaces are usually spared, and paravertebral masses are not seen except when solid extraosseous soft tissue component is associated with destructed vertebral bodies. [ 17 , 18 , 22 ] Jung et al [ 24 ] suggested that thin and smooth enhancement of abscess wall and a well defined paraspinal abnormal signal is more in favor of tubercular abscess compared with neoplasm. A study of Khattry et al [ 20 ] reported a case of tuberculous spondylitis in an adolescent was misdiagnosed as a neoplastic disease, due to multiple skip lesions involving vertebral bodies and pedicles with sparing of the intervertebral discs.…”
Section: Discussionmentioning
confidence: 99%
“…were MRI features for differentiating the cases of spinal TB and MT. 5 In our study, skip lesions and intervertebral space destruction were identified to be the two independent diagnostic factors, and included in the scoring system. For other imaging features, take paraspinal abscess as an example, it is a manifestation highly suggestive of spinal TB, but sometimes TB cases are in the developmental stage in which the abscess has not yet formed (high specificity but low sensitivity).…”
Section: Discussionmentioning
confidence: 99%
“… 1 , 4 Given the similar manifestations, differential diagnosis of the two diseases constitutes a clinical challenge. 3 , 5 , 6 …”
Section: Introductionmentioning
confidence: 99%
“…1 In our case, atypical imaging features such as spondylitis without discitis, vertebral plana with sclerosis, as well as intraspinal and epidural extra-osseous lesions involving the central and anterior vertebrae were however observed, mimicking lymphoma or tumour metastasis. 2 However, the development of paravertebral abscesses with subligamentous and epidural spread, intra-abscess calcifications, posterior element sparing and absence of skip lesions favoured tuberculosis over malignancy and other infective causes. 2 3 As such, the hepatopulmonary lesions seen on CT were therefore regarded as tuberculomas.…”
mentioning
confidence: 99%